factor 14a2 - 68a + 48

The factored form of 14a2 - 68a + 48 is: 2(7a - 6)(a - 4)

Question

Asked 3/10/2014 6:49:38 AM

Updated 3/10/2014 7:08:41 AM

1 Answer/Comment

Rating

3

The factored form of 14a2 - 68a + 48 is:

2(7a - 6)(a - 4)

2(7a - 6)(a - 4)

Added 3/10/2014 7:08:41 AM

This answer has been confirmed as correct and helpful.

Input in standard form the equation of the given line.
The line with m = 1/2 and b = 3.

Question

Not Answered

Updated 3/6/2014 8:18:47 AM

1 Answer/Comment

The line with m = 1/2 and b = 3 in standard form is x - 2y = - 6

Added 3/6/2014 8:18:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/14/2014 8:32:27 AM]

Find the solution to the equations.
2x - y = -3
x + y = 0
(0, 0),
(-1, 1),
(1, -1), **Weegy:** A.(0, 0) is the answer. x=0, y=0 **User:** 5x + 10y = 18
x = y - 6
Which of the following equations is the result of substituting y - 6 in for x in the first equation?
5x + 10y - 6 = 18,
5y - 6 + 10y = 18,
5y - 30 + 10y = 18, (More)

Question

Expert Answered

Updated 3/10/2014 8:08:23 AM

2 Answers/Comments

The solution to the equations 2x - y = -3, x + y = 0 is (-1, 1).

Added 3/10/2014 7:52:48 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/14/2014 8:32:31 AM]

5x + 10y = 18

x = y - 6, replace x in the first equation we get:

5(y - 6) + 10y = 18

so, the result of substituting y - 6 in for x in the first equation is 5y - 30 + 10y = 18

x = y - 6, replace x in the first equation we get:

5(y - 6) + 10y = 18

so, the result of substituting y - 6 in for x in the first equation is 5y - 30 + 10y = 18

Added 3/10/2014 8:08:23 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/14/2014 8:32:30 AM]

What is the slope of the line 4x + 6y = 12?

Question

Not Answered

Updated 3/13/2014 7:43:41 AM

2 Answers/Comments

The slope of the line 4x + 6y = 12 is -2/3.

Added 3/13/2014 7:43:41 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/14/2014 8:32:17 AM]

What is the equation of the line that passes through (1, 3) and (-2, -3)? **Weegy:** y=-3/4x+7/4 is the equation of the line that passes through (5, -2) and (-3, 4). **User:** (12x 2 - 10x -12) ÷ (3x + 2) **Weegy:** When you multiply and simplify (x + 4)(x^2 - 3x + 2) you get the result of x^3 + x^2 - 10x + 8. (More)

Question

Expert Answered

Updated 3/13/2014 7:21:49 AM

2 Answers/Comments

The equation of the line that passes through (1, 3) and (-2, -3) Is y = 2x + 1

Added 3/13/2014 7:17:02 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/13/2014 7:19:41 AM]

27,868,406

questions answered

There are no comments.